Chitotriosidase gene expression in Kupffer cells from patients with non-alcoholic fatty liver disease. Issue 9 (6th July 2006) - Malaguarnera, L; Di Rosa, M; Zambito, A M; dell'Ombra, N; Nicoletti, F; Malaguarnera, M
Abstract : Background and aims: Non-alcoholic steatohepatitis (NASH) is a clinicopathological condition characterised by a necroinflammatory disorder with fatty infiltration of the hepatocytes. The molecular mechanisms involved in the anomalous behaviour of liver cells have only partially been determined. Human chitotriosidase (Chit) is a chitinolytic enzyme mainly produced by activated macrophages. The aim of this study was to investigate the expression of the chitinase-like gene in Kupffer cells, to determine how chitotriosidase may be implicated in the progression from uncomplicated steatosis to steatohepatitis with progressive fibrosis. Methods: 75 subjects were studied: 40 with NASH, 20 with simple steatosis, and 15 normal controls. Kupffer cells obtained from liver biopsies were used to detect CHIT expression, superoxide anion (O2 − ), lipid peroxidation, and tumour necrosis factor α (TNFα) and ferritin levels. Results: CHIT expression differed markedly in livers from normal controls and in those from patients with simple steatosis or non-alcoholic steatohepatitis. A significant correlation between mRNA CHIT and O2 −, lipid peroxidation, TNFα, and ferritin levels was observed in both NASH and simple steatosis. Conclusions: Human Kupffer cells in NASH patients overproduce chitotriosidase. At the highest levels of production, this enzyme may play a role in increasing the risk for a poor outcome in steatohepatitis.